*London Transport Workers' Strike, 1912 (1912)
1912 1880-1914 "*London Transport Workers' Strike, 1912" [T0185.jpg], 1912 The National Transport Workers' Federation called a port-wide strike in London at the end of May 1912 to extend the gains of the 1911 strike. Ben Tillett and Ted Leggatt were, once again, prominent in the strike leadership. There were massive demonstrations and frequent violent clashes between strikers and the police or strike-breakers, but employers remained obdurate and refused to negotiate. The unions failed to extend the strike nationally, and it collapsed at the end of July.